2017
DOI: 10.3389/fpls.2017.02032
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Calcium Enhances the Photosystem II Photochemistry Response in Salt Stressed Tall Fescue

Abstract: Calcium enhances turfgrass response to salt stress. However, little is known about PSII photochemical changes when exogenous calcium was applied in salinity-stressed turfgrass. Here, we probe into the rearrangements of PSII electron transport and endogenous ion accumulation in tall fescue (Festuca arundinacea Schreber) treated with exogenous calcium under salt stress. Three-month-old seedlings of genotype “TF133” were subjected to the control (CK), salinity (S), salinity + calcium nitrate (SC), and salinity + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Previous study reported a similar trend of increment in total chlorophyll content by supplementary Ca 2? in Trigonella foenum-graecum (Oprica and Sandu 2014), Festuca arundinacea (Wang et al 2017) and rice (Tahjib-Ul-Arif et al 2018c). The addition of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported a similar trend of increment in total chlorophyll content by supplementary Ca 2? in Trigonella foenum-graecum (Oprica and Sandu 2014), Festuca arundinacea (Wang et al 2017) and rice (Tahjib-Ul-Arif et al 2018c). The addition of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, exogenous protectants, such as osmoprotectants (mannitol) (Chan, Grumet, & Loescher, ; C. Ma, Ren, Hu, Chen, & Li, ), phytohormones (Brassinosteroids, ABA) (S. Gao, Sun, Li, Shi, & Qi, ; Talaat & Shawky, ; Yue, Zhang, You, Wang, & Zhang, ), signalling molecules (hydrogen sulphide, nitric oxide, γ‐aminobutyric acid) (Deng et al, ; Dong, Jinc, Liu, Xu, & Kong, ; Khoshbakht, Asghari, & Haghighi, ; Y. Wang, Gu, et al, ), polyamines (Spd, Spm, Put) (Khoshbakht, Asghari, & Haghighi, ; Shu et al, ; Yaakoubi, Hamdani, Bekalé, & Carpentier, ), microorganisms (arbuscular mycorrhizal fungi, Bacillus subtilis ) (Han et al, ; Y. Zhang, Gao, Guo, & Hao, ), trace elements (Ca, Si, Se) (Diao et al, ; G. Wang, Bi, et al, ; G. Zhao, Li, Xing, Wang, & Chang, ) and other substances (5‐azacytidine) (Zhong, Xu, & Wang, ) have been found effective in mitigating salt‐induced damages. However, different exogenous substances may be used to enhance plant resistance, but excessive exogenous substances may adversely affect plants.…”
Section: Improving Salinity Tolerancementioning
confidence: 99%
“…Exogenous Ca 2+ ions play an important role in photosynthesis, as they determine the proper function of photosystem II (PS II-water-plastoquinone oxidoreductase), i.e., the first protein complex located in thylakoid membranes, in the light-dependent reaction of oxygenic photosynthesis, which is responsible for adaptation to stressful conditions [ 10 , 11 ]. Wang et al [ 12 ] showed the protective role of exogenous calcium, suggesting that calcium nitrate enhanced the electron transfer of PSII (especially beyond QA-) and prevented inactivation of reaction centers in salt-stressed tall fescue.…”
Section: Introductionmentioning
confidence: 99%